PEMBAGIAN HARTA WARISAN BAGI ANAK ANGKAT BERDASARKAN HUKUM ADAT DAYAK NGAJU DI KEDAMANGAN JEKAN RAYA KOTA PALANGKA RAYA - Putri Fransiska Purnama Pratiwi (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2019)
This research determine the right of an adopted child to obtain inheritance rights and the position of his biological parents in the customary law of Dayak Ngaju. The study uses a type of empirical legal research with interview methods and document review. The child is raised through the procedure of Hambai Angkat, the child's position becomes equal to the biological child. The child's has no relationship with his biological parents anymore. The position of biological parents in the distribution of children's inheritance has been illustrated from the status of adoption of the child. If the child is appointed by adoption of Hambai Angkat, his biological parents have absolutely no rights in the distribution of the adopted family's heirs to his child. Bif the child is still under age, then he is most likely will be returned to his biological parents with a